Wake up or Fall Asleep: Value Implication of Trusted Computing - HU, Nan (Institutional Knowledge at Singapore Management University, 2009)
More than 10 years have passed since trusted computing (TC) technology was introduced to the market; however, there is still no consensus about its value. The increasing importance of user and enterprise security and the security promised by TC, coupled with the increasing tension between the proponents and the opponents of TC, make it timely to investigate the value relevance of TC in terms of both capital market and accounting performance. Based on both price and volume studies, we found that news releases related to the adoption of the TC technology had no information content. All investors, regardless of whether they are individual investors or institutional investors, or they are wealthy individual investors or less wealthy individual investor, all have similar views on the value of TC. Further, we show that the accounting benefit gained from the adoption of TC is trivial, which might explain the price invariance and volume invariance we observed in the stock market.